Product Design for Manufacture and Assembly / Third Edition - Boothroyd Geoffrey; Dewhurst Peter; Knight Winston A (Crc Press, 2015)
The book provides significant savings in the product development process. Introduction, Selection of Materials and Processes, Product Design for Manual Assembly, Electrical Connections and Wire Harness Assembly, Design for High-Speed Automatic Assembly and Robot Assembly, Printed Circuit Board Design for Manufacture and Assembly, Design for Machining, Design for Injection Molding, Design for Sheet Metalworking, Design for Die Casting, Design for Powder Metal Processing, Design for Sand Casting, Design for Investment Casting, Design for Hot Forging.